Kombinasi Analytical Hierarchy Process dengan Weighted Product untuk Penerima Beasiswa Prestasi Sistem Pendukung Keputusan - Fathony, Zamzam; Saputra, Eko Rachmat Slamet .H; Frobenius, Arvin Claudy (Jurusan Teknologi Informasi Universitas Semarang, 2024)
Scholarships are an appreciation given by universities in the form of educational assistance, one of which is for prospective students who have achievements in non-academic fields. Mercu Buana University Jakarta provides as many as 20 quotas per year for merit scholarships. The decision-making process for merit scholarship recipients is still focused on manual calculation using the average value method process. Based on these problems, a study was conducted to design a decision support system using analytical hierarchy process and weighted product methods. Variables used in achievement weighting, level, test scores. The process of weighting the AHP method produces an achievement priority value of 0.260, a level of 0.633, and a test score of 0.106 and the results on the consistency criteria matrix are 0.033. The results of the WP ranking are the scores on the achievement criteria, namely -0.260, the level is 0.633 and the test score is 0.106. The results on the user acceptance test are 84.4%, it can be concluded, functionality can be accepted by users